Unraveling the mechanism of sulfur nutrition in pigeonpea inoculated with sulfur-oxidizing bacteria - Malviya, Deepti; Varma, Ajit; Singh, Udai B.; Singh, Shailendra; Saxena, Anil K. (Frontiers in Microbiology, 2022)
An investigation was carried out to understand the mechanism(s) involved in the uptake of sulfur (S) as sulfate in pigeonpea following single inoculation of two sulfur oxidizing bacteria (SOB), Stenotrophomonas maltophilia and Stenotrophomonas pavanii in the treatments amended with either elemental sulfur (S0) or sulfate (S6). Colonization potential and biofilm formation were analysed through confocal laser scanning microscope (CLSM) and scanning electron microscope (SEM). Further, the effect of seed inoculation on root architecture, expression of genes involved in sulfur oxidation (sox) in bacterial inoculants and genes involved in sulfate transport in pigeonpea (PpSULTR) were analysed to correlate with the higher uptake of S in roots and shoots of pigeonpea. Both the SOB exhibited a good colonization potential and biofilm formation on the roots of pigeonpea. Among the 11 sox genes targeted in rhizosphere of pigeonpea, expression was achieved for 7 genes, which showed two folds increase in treatments inoculated with S. maltophilia and amended with either S6 or S0. The inoculation of S. maltophilia and amendment of S0 led to increased expression of PpSULTR genes by several folds in roots. The inoculation of SOB had a significant influence on non-enzymatic (osmolytes like proline) and enzymatic (PAL, peroxidase, superoxide dismutase and catalase) levels. The results revealed a significant increase in sulfur uptake in roots and shoots in treatment inoculated with S. maltophilia and amended with S6. The investigation showed that the SOB-mediated over-expression of PpSULTR genes in roots of pigeonpea, and sox genes in the rhizosphere were acting synergistically in facilitating higher uptake and translocation of S in roots and shoots of pigeonpea plants.